The influence of testosterone on the risk of cardiovascular events after percutaneous coronary intervention - Chiang, Cheng-Hung; Hung, Wan-Ting; Liu, En-Shao; Yang, Tse-Hsuan; Cheng, Chin-Chang; Huang, Wei-Chun; Mar, Guang-Yuan; Kuo, Feng-Yu (Frontiers in Cardiovascular Medicine, 2022)
Background: This study aimed at evaluating the influence of testosterone on the risk of cardiovascular events in men after percutaneous coronary intervention (PCI) by a retrospective cohort study. Methods: Between 2015 and 2018, 580 men undergoing PCI at a tertiary referral hospital were divided into low (< 3.25 ng/mL) and normal (≥ 3.25 ng/mL) testosterone groups. Major adverse cardiovascular event (MACE) was defined as the composite outcome of cardiovascular death, myocardial infarction, and target lesion revascularization/target vessel revascularization (TLR/TVR) during up to 48 months follow-up after PCI. Results: There were 111 and 469 patients in the low and normal testosterone groups, respectively, with the overall MACE rate of the former being higher than the latter (26.13% vs. 13.01%, p = 0.0006). Moreover, the overall TLR/TVR (20.72% vs. 11.73%, p = 0.0125), and myocardial infarction (3.6% vs. 0.85%, p = 0.0255) rates were significantly higher in those with low serum testosterone who also had a shorter average event-free survival analysis of MACE (25.22±0.88 months) than those with normal testosterone levels (35.09±0.47 months, log-rank p = 0.0004). Multiple logistic regression demonstrated an association between low serum testosterone (< 3.25 ng/mL) and a higher MACE rate [odds ratio: 2.06, 95% confidence interval (CI) 1.21 to 3.51, p = 0.0081]. After adjusting for variables in a Cox regression model, hazard ratios (HRs) for MACE (HR: 1.88, 95% CI 1.20 to 2.95, p = 0.0058) and TLR/TVR (HR: 1.73, 95% CI 1.06 to 2.83, p = 0.0290) rates were higher in the low testosterone group than those in the normal testosterone group. Conclusions: Low serum testosterone concentrations were associated with a higher risk of MACE and TLR/TVR after PCI than those with normal testosterone levels.